A BUDDHIST SPIRITUAL LEADERSHIP IN PRACTICE: INSIGHTS FROM THE INDONESIAN BUDDHAYĀNA COUNCIL IN LAMPUNG PROVINCE - Juni Suryanadi; I Putu Gelgel; Wayan Paramata (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the implementation of Buddhist spiritual leadership in the Indonesian Buddhayana Council (MBI) of Lampung Province. Spiritual leadership in Buddhist teachings emphasizes the values of compassion, wisdom, exemplary behavior, and selfless service. The research method employed a qualitative approach, phenomenology, with data collection techniques through in-depth interviews, observation, and documentation studies. This research was conducted with the leadership of the MBI of Lampung Province. The results indicate that leadership in the MBI of Lampung Province, through an understanding of Buddhayana values and humanistic Buddhism, maintains internal organizational harmony, increases congregation participation, and strengthens the socio-religious role. However, challenges arise in the form of limited in-depth understanding of spiritual values and administrative pressures that can shift the focus of leadership. In conclusion, Buddhist spiritual leadership in the MBI of Lampung Province is relevant for adaptation as an organizational management model that combines spiritual values and managerial effectiveness.